The Comprehensiveness of Islamic Sharia’a: Between Negation and Affirmation - Ayad Abdul Hussein Mahdi Al Mansouri ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The study of legislative comprehensiveness is a crucial topic closely tied to Islamic Sharia’a and its various legislations and Fatawas. The comprehensiveness of Islamic Sharia’a is considered one of its most prominent characteristics and advantages over other divine and human laws. This comprehensiveness implies the ability of Islamic Sharia’a, with its vast array of legislations, to encompass all that a human being, whether as an individual or as a society, and needs in all aspects of life. It is also applicable to all times and places, leaving no aspect of life untouched by Allah’s rulings that clarify His stance on various situations. There is no event or incident that Allah does not have a specific stance on. Those who follow the rulings of Islamic Sharia’a can clearly see this comprehensiveness and inclusiveness. Moreover, they find in its legal texts an explicit and unambiguous statement of this meaning. However, comprehensiveness and inclusiveness do not imply the existence of a specific legal text that addresses the ruling of every single event with its detailed and specific titles. This is a notion that none of those who adhere to the concept of comprehensiveness have ever claimed. Rather, what is meant by comprehensiveness and inclusiveness is the ability of Islamic Sharia’a, with its general and universal principles derived from its legal texts, to encompass all the details and variables in every aspect of life. This includes the silence of the legislator regarding the legislation of an obligation or prohibition in a specific matter, as the silence of the Lawgiver indicates permissibility in that matter.